Development of Independent Learning Skills Through the Electrical Teaching Program at Mifasol: Pengembangan Keterampilan Belajar Mandiri Melalui Program Pengajaran Listrik di Mifasol - Ni Putu Devira Ayu Martini; Ayu Mika Sherila; Achmad Zuchriadi; Yosy Rachmawati; Galang Kenda Pradana; Putri Setyarini; Siti Choiriyah; Bella Sherlyana; Arif Amarudin (Universitas Muhammadiyah Sidoarjo, 2025)
Independent learning has become a crucial competency in the digital era, especially in STEM fields, where adaptability and self-direction are essential. Specifically, underprivileged and out-of-school children face barriers in acquiring such skills due to limited access to formal education. While prior research explores project-based and collaborative learning in formal settings, there remains a knowledge gap in connecting informal community-based STEM programs to national curriculum goals for marginalized learners. This study aims to examine the development of independent learning skills through the Electrical Engineering Teaching Program (TEMA) at Rumah Belajar MiFasol, a community initiative targeting educational equity. Results from participatory observation, questionnaires, and interviews with 22 participants reveal that 63.6% found the program highly beneficial, 72.7% were actively engaged, and 90.9% desired future iterations. The novelty lies in TEMA’s alignment with the Indonesian National Curriculum in an informal context, integrating core competencies and practical STEM activities like the ice cream experiment to stimulate curiosity and critical thinking. The implications suggest that structured, informal educational interventions—rooted in national standards—can bridge educational disparities and cultivate learner autonomy among underserved populations.Highlight : Empowering Out-of-School Students: The Electro Teaching Program provides access to STEM education for underprivileged children, fostering independent learning and self-confidence. Interactive and Practical Approach: Activities such as experiments and games make learning engaging and effective, aligning with national education standards. Positive Impact and Feedback: Over 90% of participants expressed high satisfaction, showing strong interest in continuing the program. Keywords : Education, Innovative Learning, STEM Program, Electro Teaching, Independent Learning